Rational design of reduced graphene oxide/TiO2/gold nanorod nanocomposite for complete degradation of polystyrene microplastics in wastewater - UshaVipinachandran, Varsha; Naveenkumar, K.; Haroon, Kabir Hussain Badagoppam; Ashokan, Indhumathi; Sinha, Arup; Maity, Pradip; Bhunia, Susanta Kumar (Advanced Sustainable Systems, 2025)
Our planet is being devoured by plastic consumption every day. Water, soil, and air are deliberately polluted by the ingredients of these nondegradable plastics. Extensive usage of plastic has serious consequences in the environment, wildlife, and human health. A comprehensive approach to eradicate plastics from the planet is therefore imperative. Herein, a ternary nanocomposite subsumed of reduced graphene oxide (rGO), titanium dioxide (TiO2), and gold nanorods (AuNRs) is synthesized and effectively deployed to remove plastics from water as well as degradation of polymer film by both chemically and photocatalytically. The hydrothermally prepared nanocomposite completely removes polystyrene molecules from water, and 1.2 mg of plastic degradation is observed during the photolysis. Conversely, chemical degradation pathway induces the weight loss of 10.7 mg. Both Plasmon-induced interfacial charge transfer transition (PICTT) and Plasmon-induced hot electron transfer (PHET) assist the formation of reactive oxygen species (ROS) that collectively degrades the polymer strands. The spectrochemical and microscopic studies validate the degradation studies with cautious conclusions.
Keywords: chemical degradation; Photocatalysis; plasmonic hot electron; polystyrene microplastics; Reduced graphene oxide

Recyclable l-glutamic acid-based polyester schiff base cross-linker for 3D printing applications - Kamble, Ganesh N.; Ghute, Aaditi P.; Asha, S. K. (ACS Applied Polymer Materials, 2026)
An l-amino acid-based polyester Schiff base cross-linker was developed from amine-functionalized polyester and biobased methacrylate vanillin. Vanillin, one of the few biobased and aromatic compounds readily available on an industrial scale, has recently garnered significant attention from the polymer community. The l-amino acid-based polyester Schiff base cross-linker (P3) was synthesized by condensing the aldehyde group of methacrylate vanillin with the amine group of the l-glutamic acid polyester. This polymeric cross-linker was used in resin formulations consisting of isobornyl acrylate as a reactive diluent and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as the photoinitiator for digital light processing (DLP) three-dimensional (3D) printing. The resulting 3D-printed parts exhibited good mechanical properties, with a Young's modulus of 1.5 GPa, and high thermal stability, with a T max of 410 degrees C. The chemical degradability of the 3D-printed materials was demonstrated in a mixture of tetrahydrofuran and diethylene triamine (1:1) at 80 degrees C for 48 h. The reusability of the recovered resin was demonstrated by adding fresh methacrylate vanillin and photoinitiator, followed by 3D printing using a DLP 3D printer. The 3D-printed parts produced from the recycled resin retained substantial mechanical properties, with a Young's modulus of 1.39 GPa, and thermal stability, with a T max of 390 degrees C.
Keywords: 3D printing; chemical degradation; covalent adaptable network; l-glutamicacid; Vanillin